High blood neutrophil-lymphocyte ratio associated with poor outcomes in miliary tuberculosis - Han, Yeji; Kim, Soo Jung; Lee, Su Hwan; Sim, Yun Su; Ryu, Yon Ju; Chang, Jung Hyun; Shim, Sung Shin; Kim, Yookyung; Lee, Jin Hwa (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: It is difficult to predict the prognosis of miliary tuberculosis (TB). We hypothesized that blood neutrophil-lymphocyte ratio (NLR) is an indicator of inflammatory status to reflect independent prognostic significance in patients with miliary TB. The aim of this study is to investigate the relationship between NLR and outcome in miliary TB. Methods: We retrospectively collected data from patients diagnosed with miliary TB in a tertiary referral hospital between January 1995 and January 2016. Results: A total of 96 patients were enrolled. Seventeen patients (18%) died during hospitalization due to miliary TB, and 9 (9%) died additionally during the 1-year follow-up period. Eighteen patients (19%) were diagnosed with acute respiratory distress syndrome (ARDS). In multiple logistic regression analyses, increased NLR was associated with ARDS [adjusted odds ratio, 1.15; 95% confidence interval (CI), 1.03–1.28]. By multivariate Cox regression analysis with adjustment of known prognostic factors including age, sex, body mass index, serum aspartate aminotransferase (AST), and hemoglobin, NLR was an independent predictor of in-hospital mortality [adjusted hazard ratio (aHR), 1.08; 95% CI, 1.03–1.13] and 1-year mortality (aHR, 1.08; 95% CI, 1.05–1.12). Conclusions: Pre-treatment NLR at admission may be a useful biomarker for mortality and development of ARDS in patients with miliary TB.